DETERMINATION OF VITAMIN CONTENT IN CRATAEGUS TURKESTANICA (TURKESTAN HAWTHORN) - M. N. Mirzaabdullayeva (Modern American Journals, 2025)
This study presents the results of a chromatographic analysis aimed at identifying and quantifying the vitamin content in the fruit of Crataegus turkestanica (Turkestan hawthorn). The research was conducted using high-performance liquid chromatography (HPLC) to determine the presence and concentration of both water-soluble and fat-soluble vitamins, including vitamin C, B1 (thiamine), B2 (riboflavin), B3 (niacin), B6 (pyridoxine), B9 (folic acid), and PP (niacinamide). The study confirmed the presence of several essential vitamins in varying concentrations, contributing to the understanding of the plant’s nutritional and therapeutic potential. The findings support the traditional medicinal use of C. turkestanica and provide a scientific basis for its incorporation into functional foods and phytopharmaceutical preparations. The methodological approach, based on reversed-phase HPLC with UV detection, demonstrated high sensitivity and accuracy for multivitamin profiling in plant matrices.
Keywords: Crataegus turkestanica, vitamin C, vitamin B1, B2, B3, PP, B6, B9, vitamins, chromatography, HPLC.